ARTIFICIAL INTELLIGENCE, PUBLIC MANAGEMENT AND BOILING FROG SYNDROME - Delgado Saldívar, Daniel (UNIVERSIDAD DE SONORA, 2021)
The technologies listed under the term “Artificial Intelligence” present a wide variation and great effectiveness, even if its use at the public administration seems to belong to the far future. However, the same technological and behavioral changes that generated new economic structures in society also generated new way to interact and pressure that may provoke a growing implementation of technological solutions that may satisfy the great variety of needs, interests and preferences of the countless groups and persons that make up society. That implementation, in the beginning seemingly slow and innocuous, will accelerate as the first experiences reveal that data governance in the public administration will be unavoidable and open the way for much more complex solutions. The public employees’ reaction to this new reality is still unknown.